Kesejahteraan hidup penduduk Kampung Mersing kanan - Zaimah Ramli; Marsitah Mohd Radzi; Mohd. Yusoff Hussain (Penerbit UKM, 2014)
On social and economic conditions of fisherman's life in Mersing, Johor, Malaysia.